Analisis Efek Penggunaan Media Belajar Pada Pembelajaran Jarak Jauh Darurat Covid 19 - Diah Oga Nusantari; Anik Pujiati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This study is a quantitative research to analyze result on distance learning during emergencies situation pandemic covid 19. The data was from basic statistics subject from 3 classes. Class A is using zoom or google meet applicatioan for real time face to face learning. The online face to face class is very intens in 2,5 hours once a week. Class B is using supplementary sheets. Supplementary sheets contain outline of course material and step by step of exercise. Whatsapp group was using for distribute supplementary sheets and for student-lecturer communication as well. Class C was combining online face to face and supplementary sheets. Comparison test with statistical analysis by using Anova showed statisticaly counting 23, 53632. on 5% significant level we got p-value is . It showed that there is a significantly difference on study results from the 3 classes. Continuing to simple effect using t test, then the comparison of learning result class B was significant differences to A class and C class. Refer to students score result average, class B was the lowerest among others. The highest results comes from class C. The effect size calculation in this study is 31,37%. It showed that learning media was in highly criteria in determine variation of student distance learning result. Considering that class C had highest score average, hence the educational must creative in combining learning media on distance learning to maximize quality of distance learning